Interplay of Inflammation and Endothelial Dysfunction in Bone Marrow Transplantation: Focus on Hepatic Veno-Occlusive Disease - Vion, Anne-Clémence; Rautou, Pierre-Emmanuel; Durand, François; Boulanger, Chantal M.; Valla, Dominique C. (Seminars in Thrombosis and Hemostasis, 2015)
Endothelial cells are unique multifunctional cells with basal and inducible metabolic and synthetic functions. Various stimuli can induce physiological or pathological changes in endothelial cell biology. Hematopoietic stem cell transplantation (HSCT) requires high-dose irradiation and/or chemotherapy and is associated with increased risk of bacterial infections and immune reactions. These factors can affect endothelial cells. This review provides an overview of the effects of HSCT on endothelial cells, based on findings observed in cultured cells as well as in patients. We first describe to what extent irradiation and chemotherapy constitute direct and indirect triggers for endothelial cell activation and injury. Then, we highlight the role of the endothelium in several complications of HSCT, including capillary leak syndrome, engraftment syndrome, transplant-associated microangiopathy, graft-versus-host disease, and diffuse alveolar hemorrhages. We also analyze in detail available data on sinusoidal obstruction syndrome, previously known as veno-occlusive disease of the liver, where liver sinusoidal endothelial cells are first injured and eventually lead to sinusoid occlusion and liver cell damage. Finally, we open the question of the possible contribution of endothelial damage to cardiovascular events occurring long after HSCT.
Keywords: endothelial cells; endothelial damage; sinusoidal obstruction syndrome; hematopoietic stem cell transplant